Nonlinear stability of two-layer non-homogeneous rectangular reservoir with a mixed load - Гусейнов, Сафар Ахли оглы (Proceedings of National Aviation University (archive), 2009)
The article deal with stopping issues from the pressure of regularly distributed diametrical forces and pressing on length of axis of two layered anti-gender right angled board. Analyses of accounts shown that taking into account of anti pedigreed affects to the marks of critical parameters 8−10 %.